Arch Asymmetry in Patients With Cleft Lip and Palate After Rehabilitation Treatment Using Stereophotogrammetry. Issue 5 (July 2021) - Pucciarelli, Maria Giulia Rezende; Toyoshima, Guilherme Hideki; Cardoso, Jefferson Freire; de Oliveira, Thaís Marchini; Neppelenbroek, Karin Hermana; Soares, Simone
Abstract : Abstract: Arch asymmetry in cleft patients is a current problem that interdisciplinary treatment aims to solve. This research proposed to analyze the final rehabilitation, according to the arch symmetry of these patients. Thirty-five patients aged between 18 and 30 years, rehabilitated with a fixed partial denture or implants in the cleft area. The analysis was performed using digitalized dental casts with a laser model scanner (R700TM; 3Shape A/S, Holmens Kanal 7, 1060, Copenhagen/Denmark), analyzed with a Vectra Analysis Module software program (VECTRA H1; Canfield Scientific, 4 Wood Hollow Road, Parsippany, NJ 07054). Three linear measurements were evaluated, incisal-canine, canine-molar, and incisal-molar distance. The Student t test was applied to test the significance ( P  = 0.05) of an observed sample by correlation coefficient test ( r -value). Female patients showed a significant correlation in arch symmetry. According to the rehabilitation treatment, patients who received implants showed a high correlation and significant symmetry at all maxillary distances. Finally, according to the cleft side in the maxillary dimensions, even though the majority of patients had clefts on the left side, only patients with a cleft on the right side showed symmetry in this area. Patients rehabilitated with implants in the cleft area showed a more symmetrical maxillary arch than those restored with fixed partial dentures. Abstract : Supplemental Digital Content is available in the text